Surgeries and Outcomes in Subluxated and Dislocated Lens in Eastern Nepal - Shrestha, Pranav; Sharma, Sadhana; Suwal, Rinkal; Joshi, Purushottam; Subedi, Prava (Nepalese Journal of Ophthalmology, 2023)
Introduction: Many ocular or systemic conditions can cause weakening of the zonules, leading to subluxation or complete dislocation of lens into the anterior chamber or vitreous cavity. Objectives: To evaluate the outcome of surgery in cases with subluxated and dislocated lens. Materials and methods: Retrospective chart review of all cases with subluxated and dislocated lens who underwent surgery in a one-year period from 2019 January to 2019 December was conducted. Demographic profile, systemic comorbidities, initial and final best corrected visual acuity (BCVA), surgical procedure were recorded along with all the intraoperative and post-operative complications. Results: A total of 62 eyes of 60 patients with mean age of 50.18 ± 15.18 years (18 to 87 years) were included with the modal duration of presentation of one week. Among these, trauma was found to be the most common etiology. Subluxation was present in 55 eyes and seven eyes had dislocation. Intracapsular Cataract Extraction (ICCE) was performed in 41 while 21 underwent Extracapsular Cataract Extraction (ECCE); and surgical intervention elicited a statistically significant (p < 0.05) improvement in the visual acuity. The BCVA was statistically better among the pseudophakic patient. Most common complication encountered intraoperatively was vitreous loss and post operatively was significant corneal edema. Conclusion: Cataract extraction in cases with subluxated and dislocated lens due to different etiology results in the improvement in the visual acuity of the patient. In cases where ECCE cannot be performed, ICCE also results in comparable visual improvement.